Electronic prescribing reduces prescription errors in Sanglah General Hospital Denpasar - Ni Luh Putu Nurhaeni; I Ketut Suarjana; I Made Ady Wirawan (Universitas Udayana, 2017)
Background and purpose: Medication error is any preventable event that may lead to inappropriate medication use or patient harm. Prescription error, one component of medication error, at Sanglah General Hospital Denpasar is high. An electronic prescribing has been piloted at Angsoka Ward, Sanglah General Hospital Denpasar to reduce prescription errors. However, the evaluation of such implementation is never been conducted. This study aims to evaluate the effect of electronic prescribing on prescription errors at Sanglah General Hospital Denpasar. Methods: An evaluation study was conducted by adopting pre and post control design at Sanglah General Hospital Denpasar. Prescription errors at Angsoka Ward where the electronic prescribing is implemented, were compared to Kamboja Ward that uses manual prescribing. Heterogeneity of patients in these two wards was comparable. Prescription samples were selected using a simple random sampling. Prescription samples prior to implementation of electronic prescribing were taken from June and July 2016, while samples after implementation were taken from March and April 2017. Prescription samples from the control group were also taken from the same periods. A total of 96 prescriptions were taken from each arm – leading to 384 prescription samples in total. Prescription error was evaluated using three requirements namely: administrative (9 components), pharmacy (5 components) and clinical (3 components). Results: Our study found that there was a significant difference of prescription errors between pre and post implementation of electronic prescribing at Angsoka Ward (p<0.05). The median values [IQR] for prescription error based on administrative requirements between pre and post intervention were 2 [3] vs. 0 [0] (p<0.001); based on pharmacy requirements were 1 [2] vs. 0 [0] (p<0.001); based on clinical requirements were 1 [2] vs 0 [0] (p<0,001). In contrast, prescription error based on administrative and pharmacy requirements in Kamboja Ward was insignificantly reduced. The median values [IQR] for prescription error based on administrative requirements between pre and post intervention were 2 [2] vs. 2 [2] (p=0.505) and based on pharmacy requirements were 1 [2] vs. 1 [1] (p=0.295). There was a significant difference of prescription errors (p<0.05) based on clinical requirements with median values [IQR] of 1 [1] vs. 1 [1]. Implementation of electronic prescribing reduced the proportion of prescription errors by 67.8%. After implementation of electronic prescribing, some errors were still apparent related to drug administration and order duplication. Conclusions: Implementation of electronic prescribing reduces prescription errors. Scaling-up of electronic prescribing followed by training on standardised prescribing practices are warranted.